A Heat‐Liquefiable Solid Precursor for Ambient Growth of Perovskites with High Tunability, Performance and Stability. Issue 8 (8th June 2022) - He, Yi; Lin, Zedong; Wang, Jian; Zhang, Kai; Xu, Xiuwen; Li, Yu; Huang, Xianzhen; Ma, Tingli; Xiao, Shuang; Yang, Shihe
Abstract: Halide perovskites are intensively studied for applications in optoelectronic devices because of their outstanding properties and relatively low cost. However, the common precursor solutions for perovskite fabrication are rather unstable in the presence of moisture and oxygen, limiting the large‐scale low‐cost production of perovskite. Herein, water is used counterintuitively to formulate an ambient stable perovskite precursor, which is peculiar in that it is solid at room temperature but becomes a liquid at 75 °C. The non‐fluidity of the precursor stemmed from the water‐assisted intermediate fiber assembly, conferring high damp air stability. Yet the heat‐liquefiability made the precursor highly processible for perovskite growth, and when guided by polyvinyl pyrrolidone coordination with Pb 2+, the perovskite can preferentially grow along the [200] direction, significantly improving the film quality. To demonstrate the utility of the precursor, it has been used to fabricate self‐driven halide perovskite photodetectors, which exhibited a low noise current of 2.0 × 10 −14  A Hz −1/2, a high specific detectivity up to 1.4 × 10 13 Jones, and high stability of 20 days of operation with only < 5% external quantum efficiency decay. This type of solid‐liquid convertible precursor opens up new opportunities for wider applications of perovskites. Abstract : Perovskite precursors are rather unstable in the presence of moisture and oxygen. Herein, water is used to formulate an ambient stable solid perovskite precursor that is highly processable due to its liquefaction properties upon heating. Through the coordination bond with Pb, polyvinylpyrrolidone guided the growth of perovskite along the (200) orientation, and the fabricated photodetectors exhibited outstanding performance in ambient air.